Adsorption of Sodium Dodecyl Sulfate onto Activated Coconut Shell-Based Adsorbent: Isothermal Remodelling (Journal of Environmental Microbiology and Toxicology, 2023)
A remodelling evaluation was conducted on the sorption isotherm data for SDS adsorption onto activated coconut shell using nonlinear regression. A total of nineteen models, including BET, Brouers-Sotolongo, Dubinin-Radushkevich, Fowler-Guggenheim, Freundlich, Fritz-Schlunder III, Hill, Henry, Jovanovic, Khan, Langmuir, Moreau, Radke-Prausnitz, Redlich-Peterson, Sips, Temkin, Toth, Unilan, and Vieth-Sladek, were employed to determine the best fit through nonlinear regression. All models were found to exhibit good fits to the data, except for the Fowler-Guggenheim, Henry and Dubinin-Radushkevich models. Statistical analysis based on error function assessments, including accuracy factor (AF), bias factor (BF), root-mean-square error (RMSE), adjusted coefficient of determination (adjR2), Bayesian Information Criterion (BIC), corrected AICc (Akaike Information Criterion), and Hannan-Quinn Criterion (HQC), revealed that the best performance was achieved by the Moreau model followed by (descending order) Unilan, Redlich-Peterson, Fritz-Schlunder III, Toth, and Langmuir. The maximum adsorption capacity estimates given by the Moreau and Langmuir models were better in line with experimental findings. The value of the maximum monolayer adsorption capacity for SDS binding to activated coconut shell according to the Langmuir’s parameter qmL was 81.93 mg g-1 (95% Confidence interval from 76.422 to 87.440), while bL (L mg-1), the Langmuir model constants was 0.10 L mg-1 (95% C.I. from 0.070 to 0.133). The value of the maximum monolayer adsorption capacity for SDS binding to activated coconut shell according to the Moreau’s parameter qmM was 90.82 mg g-1 (95% Confidence interval from 76.336 to 105.303), while b (L mg-1), the Moreau’s model constant was 0.15 L mg-1 (95% C.I. from 0.089 to 0.203) and l, another Moreau’s dimensionless constant was 0.3 (95% C.I. from -0.049 to 0.646).
Keywords: SDS; activated carbon; coconut shell; isotherms; Moreau